Zgodnja medicinska rehabilitacija poškodovancev po zlomu kolka v Splošni bolnišnici Celje - Golež, Ana (Rehabilitacija (Ljubljana), 2015)
Background: Hip fracture is one of the commonest fractures in the elderly. Due to its possible complications it is still a potentially life-threatening condition. Early medical rehabilitation is very important for the final outcome, especially early verticalisation and mobilization to walk. The treatment of the fractured hip must enable early verticalisation, weight bearing of the injured lower limb and mobility. We performed research article was to research quality of early medical rehabilitation of injured patients after hip fracture. Methods: Or retrospective study included 372 patients with hip fracture who had been hospitalized at the Department of Traumatology of the Celje General Hospital. Their medical records were retrieved from the hospital information system using the diagnosis of hip fracture as the search criterion. We collected data on age, gender, duration of the hospitalisation, type of hip fracture, choice of treatment, mobility level at discharge and the discharge destination. Results: Among the 372 patients, there were 256 women and 116 men; the mean age was 85 years (range from 19 to 98 years). The majority of the patients had pertrochanteric fractures, followed by femoral neck and subtrochanteric fractures. The majority of patients were treated operatively, only small percentage conservativel; the mortality was 2.2%. Almost one half of the patients were discharged home, one third to the extended hospital treatment, 20% to a seniors home, and 5% to other hospital departments. After discharge, one third of the patients were able to walk with crutches on a flat surface or stairs, one third with a walker, one third used a wheelchair, and 8% remained bed-ridden. The average length of stay was 10.6 days. Conclusions: Overall, the early medical rehabilitation of patients after hip fracture can be considered as successful. Patients treated with endoprosthesis or stabile internal fixation, who were allowed to walk with full weight bearing of the injured lower limb, achieved better functional outcome and had shorter length of stay.
Keywords: early medical rehabilitation; Guidelines as Topic; Hip Fractures; kakovost življenja; kolčni sklep; operacijsko zdravljenje; Quality of Life; smernice; standard of living; surgery; zgodnja medicinska rehabilitacija; zlom kolka